Le Politiche del presente (a cura di Caterina Arcidiacono) - Redazione, La camera blu (La camera blu. Rivista di studi di genere, 2014)
This monographic issue edited by Caterina Arcidiacono follows up La camera blu journal‘s on-line publishing. This number gathers together documents and contributions which help understand the challenges that contemporary society pose to women. Its purpose is to take into account how female condition is performed in a social context where relationships are far cry from the traditional patriarchal family standards. Yet, man and woman are in a context where environmental, working, and relational shapes struggle to find innovative forms of living together able to meet the needs of well-being, justice, and equality.